The Development of Labial Clusters in the Aśokan Rock Edicts - Suzuki, Yasuko (Studia Orientalia Electronica, 2021)
The original range of consonant clusters in Indo-Aryan reduced significantly over time, developing into geminates, homorganic nasal-stop clusters, and sonorant-h clusters in Middle Indo-Aryan. Early Middle Indo-Aryan, as represented in the Aśokan inscriptions, however, still maintained the original clusters, or what appear to be transitional stages of the extensive changes. Salient among those cluster changes that are observed in the Aśokan inscriptions are the changes tm, tv> tp and dv > db in Girnār in the west; sm, sv > sp in Shāhbāzgaṛhī and Mānsehrā in the north-west; and mh > mbh in Kālsī in the north and in Dhaulī and Jaugaḍa in the east. The idiosyncratic nature of these changes lies in the development of a stop from m or v, where the more usual changes would be loss or assimilation of m after a stop and of v after a stop or a sibilant, while sm and hm would normally change to mh. This paper examines the manner assimilation of the “labial” clusters (that is, the clusters with m or v that normally do not incur assimilation of the adjacent consonant) in the Aśokan Rock Edicts. It discusses the conditions, the motivation, the course of the change of m/v to a labial stop, and the dialectal differences associated with this change.